In lady liberty's shadow : the politics of race and immigration in New Jersey - Rodriguez, Robyn Magalit (Rutgers University Press, 2017)
"Home to Ellis Island, the state of New Jersey has been the first stop for many new immigrants for over a century. Yet in this diverse state that is so central to American immigration history, some of the most anti-immigrant policies in the country are being introduced. What sets New Jersey apart is that these policies are being introduced at the municipal level in the state's suburbs. Just when they thought they had achieved the "American Dream" in their suburban homes, immigrants instead experience an American nightmare. The paradox of anti-immigrant policies in a historically immigrant state like New Jersey is what Rodriguez tries to understand in her forthcoming book, In Lady Liberty's Shadow: Race and Immigration in Post-9/11 New Jersey. She examines the impact of anti-immigrant municipal ordinances on a range of immigrant groups living in different types of suburban communities from undocumented Latinos in predominantly white suburbs to long-established Asian immigrants in "majority-minority" suburbs. Rodriguez connects the contemporary phenomenon of anti-immigrant municipal ordinances to longer histories of African American exclusion. The "American Dream" that suburban life is supposed to represent rests on a racialized, segregated social order that was meant to only be enjoyed by whites. Though it is a case study of New Jersey, In Lady Liberty's Shadow, offers crucial insights that can shed new light on the national immigration debate"--